Pyogenic liver abscess caused by an atypical hypervirulent Klebsiella pneumoniae K1-ST23 in Mexico - Lucía Martínez-Hernandez; Alejandro Alvarado-Delgado; Nadia Rodríguez-Medina; Jorge Garcia-Peniche; José Juan Donis-Hernández; Ofelia Alma Perez-Rezendiz; Neli Nava-Domínguez; Luis Duarte-Zambrano; Elsa María Tamayo-Legorreta; Ulises Garza-Ramos (IDCases, 2024)
Hypervirulent K. pneumoniae infection has been raising worldwide and is one of the major causes of community-acquired pyogenic liver abscess. We described a case report of pyogenic liver abscess caused by an atypical hypervirulent (non-hypermucoviscous) K. pneumoniae K1 ST23 in a diabetic Asian patient who resided in Mexico. The susceptibility to antimicrobials, pathogenicity, molecular and genomic analysis were determined. A man from Guangdong (China) with a recent diagnosis of diabetes mellitus was admitted to the hospital, and he denied traveling in the last 3 months. A computed tomography revealed a right lobe liver abscess. On the third day after admission a Klebsiella pneumoniae isolate (14652) was obtained. The isolate corresponded to a susceptible K. pneumoniae with capsular type K1 and ST23 (CG23) and exhibited a non-hypermucoviscous phenotype. The isolate 14652 was genetically related to the globally distributed lineage ST23-KL1. This study describes the first case in Mexico of K. pneumoniae capsular type K1 and ST23 with an atypical hypervirulent phenotype.